A multicomponent frailty intervention for socioeconomically vulnerable older adults: a designed-delay study - Jang IY; Jung HW; Park H; Lee CK; Yu SS; Lee YS; Lee E; Glynn RJ; Kim DH (Clinical Interventions in Aging, 2018)
Il-Young Jang,1,2 Hee-Won Jung,3 Hyelim Park,1,2 Chang Ki Lee,4 Sang Soo Yu,2 Young Soo Lee,1 Eunju Lee,1 Robert J Glynn,5,6 Dae Hyun Kim6,7 1Department of Internal Medicine, Asan Medical Center, University of Ulsan College of Medicine, Seoul, Republic of Korea; 2PyeongChang Health Center & County Hospital, Pyeongchang, Gangwon-Do, Republic of Korea; 3Graduate School of Medical Science and Engineering, Korea Advanced Institute of Science and Technology (KAIST), Daejeon, Republic of Korea; 4Goldman Urology Clinic, Seoul, Republic of Korea; 5Division of Preventive Medicine, Department of Medicine, Brigham and Women’s Hospital, Boston, MA, USA; 6Division of Pharmacoepidemiology and Pharmacoeconomics, Department of Medicine, Brigham and Women’s Hospital, Boston, MA, USA; 7Division of Gerontology, Department of Medicine, Beth Israel Deaconess Medical Center, Boston, MA, USA Purpose: The primary aim of this study was to evaluate the effectiveness of a 6-month multicomponent intervention on physical function in socioeconomically vulnerable older adults in rural communities. As secondary aims, we evaluated the effectiveness of the intervention on frailty and other geriatric syndromes, sustained benefit at 12 months, and baseline characteristics associated with poor response. Patients and methods: This designed-delay study was conducted in 187 adults (mean age: 77 years; 75% women) who were living alone or on a low income in three rural regions of Korea. A 24-week multicomponent program that consisted of group exercise, nutritional supplementation, depression management, deprescribing medications, and home hazard reduction was implemented with a planned 6-month interval from August 2015 through January 2017. The primary outcome was physical function, measured using the Short Physical Performance Battery (SPPB) score (range: 0–12; minimum clinically important difference ≥1) at 6 months. Secondary outcomes included frailty phenotype, sarcopenia, Mini Nutritional Assessment-Short Form score (range: 0–14), Center for Epidemiologic Studies-Depression Scale score (range: 0–60), and falls. Results: At 6 months, the SPPB score increased by 3.18 points (95% CI: 2.89, 3.48) from baseline. The program improved frailty (odds ratio: 0.06; 95% CI: 0.02, 0.16), sarcopenia (odds ratio: 0.32; 95% CI: 0.15, 0.68), Mini Nutritional Assessment-Short Form score by 1.67 points (95% CI: 1.28, 2.06), and Center for Epidemiologic Studies-Depression Scale score by -3.83 points (95% CI: -5.26, -2.39), except for fall (rate ratio: 0.99; 95% CI: 0.69, 1.43). These beneficial effects were sustained at 12 months. Body mass index ≥27 kg/m2 and instrumental activities of daily living disability at baseline were associated with poor improvement in the SPPB score. Conclusion: This 24-week multicomponent program had sustained beneficial effects up to 1 year on physical function, frailty, sarcopenia, depressive symptoms, and nutritional status in socioeconomically vulnerable older adults in rural communities. (ClinicalTrials.gov, NCT 02554994) Keywords: clinical trial, exercise, frailty, geriatric assessment, malnutrition, public health practice